2011
DOI: 10.32890/mjli.8.2011.7626
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Social Support in Promoting Adolescents' Classroom Cognitive Engagement Through Academic Self-Efficacy

Abstract: Purpose – The main aim of the present investigation was to examine the role of teacher, peer, and parental academic and emotional support in predicting adolescent cognitive engagement, especially within the context of ESL classrooms.   Method – The present study examined the availability of academic and emotional support from teachers, classmates and parents as perceived by adolescents, via instruments which were adapted from a number of established measures. This cross-sectional study utilized the survey meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…Furthermore, adolescents are reported to experience higher academic self-concept when they perceive maternal psychological control as providing satisfaction for the adolescent's needs for autonomy, relatedness and competence (Lu, Walsh, White, & Shield, 2017). Sahil and Hashim (2011) concluded that parents' social support for children affects their levels of school engagement through the mediating role of academic self-concept. In a recent study, teachers' higher expectations were associated with higher academic self-concept in students, which in turn predicted their higher achievement (Szumski & Karwowski, 2019).…”
Section: The Role Of School Engagementmentioning
confidence: 99%
“…Furthermore, adolescents are reported to experience higher academic self-concept when they perceive maternal psychological control as providing satisfaction for the adolescent's needs for autonomy, relatedness and competence (Lu, Walsh, White, & Shield, 2017). Sahil and Hashim (2011) concluded that parents' social support for children affects their levels of school engagement through the mediating role of academic self-concept. In a recent study, teachers' higher expectations were associated with higher academic self-concept in students, which in turn predicted their higher achievement (Szumski & Karwowski, 2019).…”
Section: The Role Of School Engagementmentioning
confidence: 99%
“…This is assumed because unless the knowledge and skills are accompanied by empowering self-efficacy beliefs, they are unlikely to take learners far: Bandura [7] warned that "skills can be easily overruled by selfdoubts, so that even highly talented individuals make poor use of their capabilities under circumstances that undermine their beliefs in themselves". Indeed, Sahil and Hashim [16] indicated that educational institute outcomes are enhanced when learners feel supported and have faith in their capabilities. Ordinary students can achieve amazing results when their knowledge and talent are accompanied by strong faith in their own abilities.…”
Section: The Potentiality Of Self-efficacy Beliefsmentioning
confidence: 99%
“…No entanto, não se pode ignorar que a percepção dos estudantes aponta que não têm apoio nem abertura da escola para que possam pôr em prática as ações que acreditam ser capazes de realizar e que podem contribuir com a melhoria do ambiente. O que tem sido encontrado é a divergência entre o que os estudantes acreditam e precisam e os recursos disponibilizados pelo contexto, pois, geralmente, os adolescentes tentam envolver-se nas tomadas de decisões com base em relações e ações adotadas por adultos, entretanto, como as escolas têm exercido um controle social, não abrem espaço para o protagonismo de seus estudantes (Sahil & Hashim, 2011;Krauss, Kornbluh, & Zeldin, 2017).…”
Section: Sempre Pensei Que Deveríamos Ter Mais Informações Sobre Facu...unclassified